Associations of physical activity with sleep satisfaction, perceived stress, and problematic Internet use in Korean adolescents - Park, Subin (BMC public health, 2014)
Background The association of physical activity (PA) with sleep quality, perceived stress, and problematic Internet use was examined in a nationwide sample of Korean adolescents. Methods Data from the 2010 Korean Youth Risk Behavior Web-based Survey collected from 73,238 Korean adolescents aged 12–18 years (mean age 15.06 ± 1.75 years) were analyzed. Participants were asked to rate the frequency with which they engaged in moderate and vigorous PA per week. The risk of problematic Internet use was assessed with the Korean Internet Addiction Proneness Scale for Youth-Short Form. Self-report questionnaires were used to assess levels of sleep satisfaction and perceived stress. The associations of PA with sleep satisfaction, perceived stress, and problematic Internet use were assessed with multiple logistic regression analysis. Then, the Sobel test was used to explore the mediation of the relationship between PA and problematic Internet use by sleep satisfaction and stress. Results Physically active subjects were more likely to express satisfaction with their sleep ( AOR = 1.13; 95% CI = 1.08, 1.18), less likely to feel stress in their lives ( AOR = 0.89, 95% CI = 0.86, 0.93), and less likely to be a problematic Internet user ( AOR = 0.78; 95% CI = 0.73, 0.82) compared to physically inactive subjects. The Sobel test revealed that the inverse association between PA and problematic Internet use was partially mediated by increased sleep satisfaction or decreased perceived stress ( Z = −4.315, p < 0.001). Conclusions The results of the present study indicate a negative association between level of physical activity and risk of problematic Internet use via the mediation of sleep satisfaction and stress in Korean adolescents. Physical activity may be helpful to improve adolescent mental health.